The Influence of Empathy on Moral Judgments - Avsar, Rojhat; Gabriel , Rami (Journal of Economics and Behavioral Studies, 2021)
Empathy is expected to correlate with pro-social attitude s, but what effect does empathy have on judgments of distributive fairness? In our study, we found that participants with higher empathy scores on the Interpersonal Reactivity Index (IRI) were more likely to: (a) favor the use of egalitarian distribution when the joint effort is involved, and (b) deem overly self-interested or opportunistic behavior unfair. Female participants were more consistent in the exercise of moral judgments across diverse scenarios. Furthermore, empathy has several dimensions (e.g., perspective-taking or empathetic concern) and we observed that they interacted with gender and the nature of the hypothetical problem differently in some cases. Although the findings of the study are not counterintuitive, it has identified some avenues for further explorations and highlighted some potential methodological shortcomings of the IRI as a measure of empathetic traits.